2009
DOI: 10.1038/aps.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

Rat neuronal nicotinic acetylcholine receptors containing α7 subunit: pharmacological properties of ligand binding and function

Abstract: Aim:To compare pharmacological properties of heterologously expressed homomeric α7 nicotinic acetylcholine receptors (α7 nAChRs) with those of native nAChRs containing α7 subunit (α7* nAChRs) in rat hippocampus and cerebral cortex. Methods: We established a stably transfected HEK-293 cell line that expresses homomeric rat α7 nAChRs. We studies ligand binding profiles and functional properties of nAChRs expressed in this cell line and native rat α7* nAChRs in rat hippocampus and cerebral cortex. We used [ 125 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…In fact, while acute nicotine pretreatment protected against Meth-induced decreases in [ 3 H]mazindol binding sites in wild-type mice, nicotine had no effect in ␣4 nACh receptor subunit knockout mice (Ryan et al, 2001). In addition, there is evidence that nicotine has a greater affinity for nACh receptors containing the ␣4 subunits (Xiao et al, 2009), suggesting that nicotine affords protection through the activation of nACh receptors containing ␣4 subunits, whereas ACh affects glutamate release and excitotoxicity through the ␣7 receptor. Escubedo et al (2005) suggested that MLA protects against Meth-induced striatal dopaminergic damage in mice through the attenuation of Meth-induced oxidative stress; however the initiation of a pro-oxidant process was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while acute nicotine pretreatment protected against Meth-induced decreases in [ 3 H]mazindol binding sites in wild-type mice, nicotine had no effect in ␣4 nACh receptor subunit knockout mice (Ryan et al, 2001). In addition, there is evidence that nicotine has a greater affinity for nACh receptors containing the ␣4 subunits (Xiao et al, 2009), suggesting that nicotine affords protection through the activation of nACh receptors containing ␣4 subunits, whereas ACh affects glutamate release and excitotoxicity through the ␣7 receptor. Escubedo et al (2005) suggested that MLA protects against Meth-induced striatal dopaminergic damage in mice through the attenuation of Meth-induced oxidative stress; however the initiation of a pro-oxidant process was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-, Carbachol-, and Choline-induced Up-regulation of Other nAChR Subtypes-We also tested nicotine-, carbachol-, and choline-induced up-regulation of several other nAChR subtypes, ␣3␤4, ␣7, ␣4␤4, ␣6␤2, and ␣3␤2 nAChRs stably expressed in HEK293 cells (39,43). Concentrations of nicotine, carbachol, and choline that resulted in nearly maximal or maximal up-regulation of ␣4␤2 receptors after 24 h ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Culture and Treatment-HEK293 cells were maintained and grown as described previously (39,42,43). Cell culturing medium contained Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, 100 units/ml penicillin G, 100 g/ml streptomycin, and 0.7 mg/ml Geneticin (G418).…”
Section: H]qnb) and ␣-[mentioning
confidence: 99%
“…Stably transfected HEK 293 cells expressing rat α7 neuronal nAChRs were prepared as described previously (Moaddel et al 2008;Xiao et al 2009). The cell line was maintained at 37°C with 5% CO 2 in the incubator.…”
Section: Cell Transfection and Culturementioning
confidence: 99%
“…The patch electrodes, pulled from borosilicate glass capillaries (Sutter Instrument Company, Novato, CA, USA), had a resistance of 2.5-3.5 MΩ when filled with an internal solution containing 110 mM Tris phosphate dibasic buffer, 28 mM Tris base, 11 mM EGTA, 2 mM MgCl 2 , 0.1 mM CaCl 2 , and 4 mM Mg-ATP (pH adjusted to 7.3 with Tris base; Abdrakhmanova et al 2008;Xiao et al 2009). In some cells, ∼85% of electrode resistance was compensated electronically, so that the effective series resistance in the whole-cell configuration was accepted when less than 20 MΩ.…”
Section: Whole-cell Current Recordingmentioning
confidence: 99%